(untitled) (In situ, 2024)
In October 2022, archaeological supervision was carried out over the excavation of the canal for the electricity and water supply connection of the old Technical School building. The supervision covered Stratico, Bartola Kašića and Šime Vitasovića streets. With this excavation, previously detected buttresses were explored in their full length, and it seems that the dig also encompassed a part of the fifth buttress, which was previously unknown. Remains of a cobble pavement in a length of 11 meters with interruptions due to damage were found to the southwest of the building during the supervision of the excavation for the water supply connection.